Novel NiO/RP composite with remarkably enhanced photocatalytic activity for H2 evolution from water. (28th May 2021) - Chen, Nannan; Cao, Jing; Guo, Minna; Liu, Chang; Lin, Haili; Chen, Shifu
Abstract: The low photocatalytic activity of red phosphorus (RP) for H2 production seriously restricts its wide application. In this work, we reported a facile synthesis and remarkable activity improvement of NiO/RP composite for water splitting. As a result, the 3% NiO/RP composite exhibited the highest photocatalytic activity for H2 production (57.27 μmol g −1 h −1 ), which is 68.56 times higher than that of pure RP (0.82 μmol g −1 h −1 ) under visible light (λ ≥ 420 nm) irradiation. The investigation of photocarriers separation mechanism indicated NiO/RP composite applied a Z-scheme mechanism to promote the photocarriers separation. This is a potential strategy to dramatically enhance the photocatalytic activity of RP for H2 evolution using transition metal oxide to efficiently separate the photocarriers under light irradiation. Graphical abstract: NiO remarkably enhanced the photocatalytic activity of RP for H2 evolution through a Z-scheme mechanism to separate photocarriers under light irradiation. Image 1 Highlights: Novel NiO/RP composites were firstly reported. NiO/RP showed much higher activity for H2 generation than pure RP. A Z-scheme mode was proposed for the photocarriers separation of NiO/RP.